Preparation of purine functionalized biochar and analysis of nephrotoxic substances in traditional Chinese medicine - Yanhui Ge; Xinya Xu; Yuanru Zheng (Journal of Holistic Integrative Pharmacy)
In recent years, a growing lack of comprehension regarding the safety of traditional Chinese medicines (TCMs) has led to an escalating incidence of drug-induced organ damage, particularly kidney damage associated with TCM usage. This study focused on the development of purine-functionalized biochar and used to capture nephrotoxic substances in TCMs. The biochar was meticulously characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and elemental analysis. Subsequently, it was employed as a solid-phase extraction medium for capturing suspected nephrotoxic substances in TCMs. Results revealed that the functional biochar exhibited commendable selectivity for compounds with nephrotoxic effects, demonstrating its potential for effectively capturing nephrotoxic substances in TCMs. This research aimed to introduce an innovative method for monitoring potential nephrotoxic substances in large-scale TCMs, thereby contributing to the enhancement of the overall safety profile of traditional Chinese medicine.